C,B,R, for Sandy and Silt-Clay Subgrades - Ordoñez Huaman, Abel (2001)
Currently in Peru, the design of pavement structures generally considers support capacity values ​​of sandy and silt-clayey subgrades determined fromof laboratory tests CBR- ASTM DI883.The methodology used may not be adequately applied when the C.B.R. value is assumed.of the subgrade related to the dry density equivalent to 95% 6 100% of the Maximum Dry Density - MDS of the Modified Proctor test.The humidity and natural dry density of silt-clay soils have an important influence on the determination of the C.B.R. as has been confirmed in tests on unaltered and compacted samplesComparisons of C.B.R. values ​​were made. obtained from unaltered and compacted samples considering 95% and 100% of the MDS of the Modified Proctor test. Likewise, values ​​of elastic moduli were compared, using an extension of elastic theory.The results indicate that the values ​​of C.B.R. and elastic moduli obtained in samplesunaltered are significantly lower than those determined in compacted samples.The engineering practice for determining the C.B.R. of the subgrade based on unaltered samples is almost not used in Peru, due to this, premature failures of pavements occur due to under-sizing in the design.